How do you do (a) and (b)?

Bernoulli’s equation is an equation of the form y ′ = a(t)y + f(t)y n , where n can't be 0 or 1.

(a) Using the substitution z = y 1−n , show that we can transform Bernoulli’s equation into the linear equation z ′ = (1 − n)a(t)z + (1 − n)f(t).

(b) Solve the equation xy′ + y = x^4 y^3

Respuesta :

Answer:

See solution below

Step-by-step explanation:

(a) If n=0 or 1, the equation

(1)  [tex] y' = a(t)y + f(t)y^n [/tex]

would be a simple linear differential equation. So, we can assume that n is different  to 0 or 1.

Let's use the following substitution:

(2) [tex]z=y^{n-1}[/tex]

Taking the derivative implicitly and using the chain rule:

(3) [tex]z'=(1-n)y^{-n}y'[/tex]

Multiplying equation (1) on both sides by

[tex](1-n)y^{-n}[/tex]

we obtain the equation

[tex](1-n)y^{-n}y' = (1-n)y^{-n}a(t)y+(1-n)y^{-n}f(t)y^n[/tex]

reordering:

[tex](1-n)y^{-n}y' = (1-n)y^{-n}ya(t)+(1-n)y^{-n}y^nf(t)[/tex]

[tex](1-n)y^{-n}y' = (1-n)y^{1-n}a(t)+(1-n)y^{0}f(t)[/tex]

[tex](1-n)y^{-n}y' = (1-n)y^{1-n}a(t)+(1-n)f(t)[/tex]

Now, using (2) and (3) we get:

[tex]z'= (1-n)za(t)+(1-n)f(t)[/tex]

which is an ordinary linear differential equation with unknown function z(t).

(b)

The equation we want to solve is

(4)   [tex]xy'+ y = x^4 y^3[/tex]  

Here, our independent variable is x (instead of t)

Assuming x different to 0, we divide both sides by x to obtain:

[tex]y'+\frac{1}{x}y = x^3 y^3[/tex]

[tex]y' = -\frac{1}{x}y+x^3 y^3[/tex]

Which is an equation of the form (1) with

[tex]a(x)=-\frac{1}{x}[/tex]

[tex]f(x)=x^3[/tex]

[tex]n=3[/tex]

So, if we substitute

[tex]z=y^{-2}[/tex]

we transform equation (4) in the lineal equation

(5) [tex]z'=\frac{2}{x}z-2x^3[/tex]

and this is an ordinary lineal differential equation of first order whose

integrating factor is

[tex]e^{\int (-\frac{2}{x})dx}[/tex]

but

[tex]e^{\int (-\frac{2}{x})dx}=e^{-2\int \frac{dx}{x}}=e^{-2ln(x)}=e^{ln(x^{-2})}=x^{-2}=\frac{1}{x^2}[/tex]

Similarly,

[tex]e^{\int (\frac{2}{x})dx}=x^2[/tex]

and the general solution of (5) is then

[tex]z(x)=x^2\int (\frac{-2x^3}{x^2})dx+Cx^2=-2x^2\int xdx+Cx^2=\\\ -2x^2\frac{x^2}{2}+Cx^2=-x^4+Cx^2[/tex]

where C is any real constant

Reversing the substitution  

[tex]z=y^{-2}[/tex]

we obtain the general solution of (4)

[tex]y=\sqrt{\frac{1}{z}}=\sqrt{\frac{1}{-x^4+Cx^2}}[/tex]

Attached there is a sketch of several particular solutions corresponding to C=1,4,6

It is worth noticing that the solutions are not defined on x=0 and for C<0

Ver imagen rodolforodriguezr
ACCESS MORE

Otras preguntas